Repositioning of fluoxetine as anti-virulence agent against Pseudomonas aeruginosa - Syed Mohd Danish Rizvi; Amr Selim Abu Lila; Afrasim Moin; Shahanawaz Syed; Daniya Fatima; El-Sayed Khafagy; Azza A. H. Rajab; Wael A. H. Hegazy (Future Journal of Pharmaceutical Sciences, 2025)
Abstract Background The bacterial resistance is an increasing obstacle against the global health that necessitates innovation of new approaches. Targeting bacterial resistance is one of the promising approaches. Pseudomonas aeruginosa is a clinically significant opportunistic pathogen and causes wide diverse of illness. The P. aeruginosa virulence is regulated by several systems as quorum sensing (QS) systems. Additionally, P. aeruginosa could employ membranal sensors to sense the neurotransmitters enhancing the virulence. Fluoxetine (FLU), an antidepressant, functions by inhibiting the reuptake of the neurotransmitter serotonin. This study aimed to assess the anti-virulence activity of FLU against P. aeruginosa. The effect of FLU at sub-inhibitory concentration was evaluated on the biofilm formation, removal of preformed biofilms, production of virulence factors such as protease, hemolysins, elastase, rhamnolipids, motility, pyocyanin, and pyoverdine. The impact of FLU on the expression of virulence-related genes was estimated. An invasion assay and mice protection assay were conducted to assess the FLU’s diminishing effect on P. aeruginosa pathogenesis. Results The results showed significant ability of FLU to inhibit the biofilm formation, bacterial motility, and production of virulence factors. These antibiofilm and anti-virulence activities of FLU were owed to the downregulation of genes involved in expression of QS systems and bacterial espionage. FLU significantly lowered the bacterial invasion and protected mice from P. aeruginosa. Additionally, synergistic outcome was obtained when FLU was combined with antibiotics. Conclusion FLU exhibits potent antibiofilm and anti-virulence effects at sub-MIC levels, likely mediated by its inhibition of QS systems. These results position FLU as a promising candidate for adjuvant therapy against drug-resistant P. aeruginosa infections.